Magnetic and critical properties of Pr0.6Sr0.4MnO3 nanocrystals prepared by a combination of the solid state reaction and the mechanical ball milling methods. (6th June 2018) - Dung, Nguyen Thi; Linh, Dinh Chi; Yen, Pham Duc Huyen; Yu, Seong Cho; Van Dang, Nguyen; Thanh, Tran Dang
Abstract: Influence of the crystallite size on the magnetic and critical properties of nanocrystals has been investigated. The results show that Curie temperature and magnetization slightly decrease with decreasing average crystallite size . Based on the mean-field theory and the magnetic-field dependences of magnetization at different temperatures, we pointed out that the ferromagnetic-paramagnetic phase transition in the samples undergoes the second-order phase transition with the critical exponents (, , and ) close to those of the mean-field theory. However, there is a small deviation from those expected for the mean-field theory of the values of, and obtained for the samples. It means that short-range ferromagnetic interactions appear in the smaller particles. In other words, nanocrystals become more magnetically inhomogeneous with smaller crystallite sizes that could be explained by the presence of surface-related effects, lattice strain and distortions, which lead the strength of ferromagnetic interaction is decreased in the small crystallite sizes.